GENETIC ANALYSIS OF SEED SIZE AND SEED RELATED TRAITS IN SELECTED GROUNDNUT (Arachis hypogaea L.) GENOTYPES - Votapwa, I. Oliver; Usman, Alhassan; Katung, Maryamu D.; Binta, Abdullaziz, F.; Gangkwi, Godwin; Ismail, S. Nassarawa; Jibrin, I. Mangwa; Tijjani, Mustapha; Abubakar, Ahmad Y.; Alhaji, Tanimu S.; Ibrahim, Abubakar U.; Muhammad, Aliyu Z.; et al. (FUDMA JOURNAL OF SCIENCES, 2025)
Breeding groundnut genotypes with larger seed size enhances consumer appeal. This study investigated the genetic variability, inheritance, and relationships of seed size and yield-related traits in Arachis hypogaea L. using a five-parameter genetic model and correlation analysis. Two crosses, ICGV 188105 × Samnut 24 (Cross 1) and its reciprocal (Cross 2), were evaluated to F3 generations at Institute for Agricultural Research (IAR), Samaru, during the 2021/2022 season. Significant variation was observed for seed size (SS1.506 mm), seed length (SL; 11.187 mm), seed width (SW; 7.409 mm), pod length (PL; 26.978 mm), hundred seed weight (100-SW; 42.705 g), and hundred pod weight (100-PW; 93.238 g). High broad-sense heritability (H² > 70%) and moderate to high phenotypic (PCV: 6.33%–38.36%) and genotypic coefficients of variation (GCV: 5.89%–38.79%) suggest strong potential for genetic improvement, particularly in Cross 2. Additive, dominance, and epistatic effects were significant for seed size and related traits, indicating complex genetic control. Strong positive correlations (p < 0.001) were observed between SS and SL (r = 0.87–0.90), SW (r = 0.85–0.91), 100-SW (r = 0.81–0.83), and 100-PW (r = 0.69–0.93), while flowering time showed weak, non-significant associations. These findings highlight promising opportunities for selecting larger seeds and related traits while allowing independent manipulation of flowering time.  We recommend implementing recurrent selection to capitalize on additive effects while maintaining heterozygosity, with Cross 2 showing superior potential for developing varieties with larger seeds and higher yield simultaneously.
Keywords: Correlation; Gene effect; Groundnut; Heritability; Seed size; Yield